Encyclopedia of world cultures: Vol.6 - Russia and Eurasia / China (G.K. Hall, 1991)
The book describes summaries of the cultures, which provide a mix of demographic, historical, social, economic, political, and religious information on the cultures of Northern Eurasia, Artic Sea, the deserts of Turkestan. It emphasizes the ways of life of the people - both past and present - and the factors that have caused the culture to change over time and place. The book also contains maps pinpointing the current location of the cultures described. the first map is an overview, showing the countries in that region. The other maps provide more detail by making the locations of the cultures in subregions